Sustainable dairy production - Jong, Peter de, 1965- (Wiley, 2013)
This book offers a comprehensive overview of the state of the art in sustainable dairy production, helping the industry to develop more sustainable dairy products, through new technologies, implementing life cycle analysis, and upgrading and optimization of their current production lines. It aims to stimulate process innovations, taking into account environmental, economic and public relations benefits for companies.